Inhibitors in Severe Hemophilia A: 25-Year Experience in Slovakia - Batorova, Angelika; Jankovicova, Denisa; Morongova, Anna; Bubanska, Eva; Prigancova, Tatiana; Horakova, Julia; Machyniakova, Marianna; Cervenka, Jan; Chandoga, Jan; Böhmer, Daniel; Mistrik, Martin (Seminars in Thrombosis and Hemostasis, 2016)
We present 25-year experience with inhibitors in previously untreated patients (PUPs) with severe hemophilia A in Slovakia, where safe factor VIII (FVIII) concentrates have been used since 1990. A prospective study focused on inhibitor incidence in PUPs was established in 1997. Out of a total 61 PUPs born between January 1997 and October 2015, 59 were eligible for evaluation; 50 and 9 were treated with > 20 exposure days (ED) of plasma-derived FVIII (pdFVIII) and recombinant FVIII (rFVIII) products, respectively. In the entire group 13/59 (22%) PUPs developed inhibitors; i.e. 7/50 (14%) and 6/9 (67%) treated with pdFVIII and rFVIII, respectively. Univariate analysis of inhibitor risk factors in patient groups with and without inhibitors showed the rFVIII and serious/recurrent infections within the first 50 EDs to be associated with inhibitor development (OR of 12.3 [95% CI 2.48–60.83; p = 0.002] and 5.0; [95% CI 1.16–21.9; p = 0.03), respectively]). Also, in multivariate Cox regression analysis, peak treatment ≥ 5 EDs reached statistical significance. The hazard ratio (HR) was 7.15 (95% CI 1.65–31.36) p = 0.0086 for rFVIII and 4.38 (95% CI 1.02–18.67) p = 0.046 for intensive treatment. Between 1993 and 2015, 21 immune tolerance inductions (ITIs) in 19 inhibitor patients were performed in the two largest hemophilia centers in Slovakia. In all but one ITI courses pdFVIII containing von Willebrand factor (FVIII/VWF) was used with preferred use of high-dose ITI (HD ITI) in high responders (HRs). Complete or partial success was achieved in 17/19 (89.5%) patients. Evaluating only the patients who already completed ITI, the success rate was even higher (15/16; 94%), including 7/7 low responders and 8/9 HR. Conclusion: Our national prospective study comprising entire group of PUPs with severe hemophilia A showed higher incidence of inhibitors in patients treated with rFVIII and those with intensive therapy within first 50 EDs. However, our experience is limited to small numbers of patients; thus, our results must be interpreted cautiously. High success rate of the ITI in our inhibitor patients has been achieved with FVIII/VWF concentrates and preferred use of HD ITI in HR patients.
Keywords: severe hemophilia A; PUPs; inhibitors incidence; immune tolerance induction